2016
DOI: 10.1109/tie.2016.2585568
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Topology and Operation of a Step-Up Multilevel Inverter With a Single DC Source

Abstract: the current study is an attempt to present a multilevel inverter based on a modular structure with a single DC source. This inverter is a switched-capacitor topology, which controls the charging as well as the discharging of the capacitors in the predetermined time intervals. The most important attribute of this multi-stage structure is the multiple charging capacities of the capacitors at each stage compared with those of the previous stages, which can ultimately increase the output voltage of the low input D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 30 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…animal's aerobic scope [45]. Thermal stress was already shown to cause behavioral changes that are usually followed by reduced ability to exploit resources [46], decreased immunity response [47,48], reproductive losses [6,49], and failure to recognize environmental cues [50,51]. A recent study on butterflyfishes showed reduced aggression due to reef's complexity loss [4].…”
Section: Plos Onementioning
confidence: 99%
“…animal's aerobic scope [45]. Thermal stress was already shown to cause behavioral changes that are usually followed by reduced ability to exploit resources [46], decreased immunity response [47,48], reproductive losses [6,49], and failure to recognize environmental cues [50,51]. A recent study on butterflyfishes showed reduced aggression due to reef's complexity loss [4].…”
Section: Plos Onementioning
confidence: 99%
“…Authors in [22] presented a switched capacitor multilevel inverter; this circuit can generate higher number of voltage levels with fewer switches in asymmetric configuration, but the TSV of the structure is significant. By the simultaneous charging and discharging of capacitors, authors in [23] obtained multilevel output voltage. However, it requires a large number of bidirectional switches and it also increases the TSV of the circuit significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In these topologies, the dc sources are minimised by using capacitors. Similarly, the topologies of [79–82] comprise only a single dc source. Some other topologies are presented in [83–85], which are the combination of dc sources and capacitors to curtail the dc sources.…”
Section: Introductionmentioning
confidence: 99%